2016
DOI: 10.1016/s0140-6736(16)31339-3
|View full text |Cite|
|
Sign up to set email alerts
|

Adalimumab for prevention of uveitic flare in patients with inactive non-infectious uveitis controlled by corticosteroids (VISUAL II): a multicentre, double-masked, randomised, placebo-controlled phase 3 trial

Abstract: (2016). Adalimumab for prevention of uveitic flare in patients with inactive non-infectious uveitis controlled by corticosteroids (VISUAL II): a multicentre, double-masked, randomised, placebo-controlled phase 3 trial. Lancet, 388(10050) Link to publication record in Explore Bristol Research PDF-document This is the author accepted manuscript (AAM). The final published version (version of record) is available online via Elsevier at http://www.sciencedirect.com/science/article/pii/S0140673616313393. Please refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
379
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 418 publications
(405 citation statements)
references
References 29 publications
15
379
0
11
Order By: Relevance
“…23 Most recently, the main study data from VISUAL I and VISUAL II studies also demonstrated the efficacy and safety of adalimumab (anti-TNFα) to treat uveitis. 13,14 Low adalimumab immunogenicity was observed in both VISUAL I and VISUAL II studies and was in the range of rates observed in other disease states. 13,14 The safety profile of adalimumab was similar to the established safety profile for approved adalimumab indications, 24 and the rates of AEs were similar compared with placebo.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…23 Most recently, the main study data from VISUAL I and VISUAL II studies also demonstrated the efficacy and safety of adalimumab (anti-TNFα) to treat uveitis. 13,14 Low adalimumab immunogenicity was observed in both VISUAL I and VISUAL II studies and was in the range of rates observed in other disease states. 13,14 The safety profile of adalimumab was similar to the established safety profile for approved adalimumab indications, 24 and the rates of AEs were similar compared with placebo.…”
Section: Discussionmentioning
confidence: 95%
“…13,14 Low adalimumab immunogenicity was observed in both VISUAL I and VISUAL II studies and was in the range of rates observed in other disease states. 13,14 The safety profile of adalimumab was similar to the established safety profile for approved adalimumab indications, 24 and the rates of AEs were similar compared with placebo. In participants with active uveitis (VISUAL I), the overall rates of adalimumab-associated AEs were higher than the placebo group, as were serious AEs and AEs leading to discontinuation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Patients with bilateral uveitis but no active systemic disease could be treated using either a local or a systemic approach. Although the inclusion criteria for the clinical trials of these drugs [46][47][48] were not limited by these factors, our clinical experts suggest that clinicians may have selected patients for the trials accordingly.…”
Section: Place Of the Interventions In The Treatment Pathwaymentioning
confidence: 99%